KIMOSPHERE 5.0 - Polydorou, Doros; Birringer, Johannes; Danjoux, Michelle (My University, 2017)
Dap Lab has been invited to present the Kimosphere Series as part of the “Staging Atmospheres” event held at Senate House and Queen Mary University. Visitors are invited to enter the immersive space, wear the HTC Vive headset and enter into the augmented virtuality of the tamarind forest on Malagasy island - the environment where our fictional narrative conjures the Red Ghosts architecture staged around the theatre space.
Keywords: Virtual Reality, Digital Performance